Manajemen Sarana dan Prasarana di TKIT Maulana Yusuf - Nabila, Syafiatun; Farihin, Ahmad; Yuliana, Yuliana (Al-Abshar: Journal of Islamic Education Management, 2023)
This article aims to explain about the management of infrastructure facilities at TKIT Maulana Yusuf. This research method is qualitative with a field approach, The results of this study explain that the management of infrastructure facilities at TKIT Maulana Yusuf which is named through the process of planning infrastructure facilities by analyzing learning materials, all teachers gather in the office to make RPP (Learning Process Plan), the second process of Procurement of Infrastructure Facilities is fairly adequate starting from the blackboard, adequate tables and chairs so that children are comfortable in the learning process without fighting for benches with their friends, the third process of Distributing Infrastructure Facilities with ATK (Office Stationery) used by teachers when teaching and distributing air conditioners and fans in class, the fourth process of Infrastructure Maintenance is very good, the condition of the classroom is very clean and comfortable, the fifth Invent process... the fifth process of Inventory of infrastructure facilities, which is all included in education if there are damaged or unfit for use items will be immediately replaced or repaired, the six processes of Elimination of Infrastructure Facilities are only cleaning equipment, the seventh process of Evaluation of facilities and infrastructure is carried out once every semester, one example is the change of independent curriculum. So for infrastructure facilities at TKIT Maulana Yusuf is quite adequate.